Effects of the RADEC learning model and cultural integration on early childhood mathematics achievement - Putri, Elsy Assari; Rakimahwati; Utoyo, Setiyo; Mahyuddin, Nenny (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to examine the effects of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model and local cultural integration on early childhood mathematical development. The research specifically analyzes the independent and interaction effects of instructional model and cultural context on children’s mathematical performance. Method: A quantitative approach was employed using a 2×2 factorial experimental design. The participants consisted of 52 kindergarten children divided into four groups: RADEC with cultural integration, RADEC without cultural integration, conventional learning with cultural integration, and conventional learning without cultural integration. The cultural component incorporated elements of Minangkabau traditions into mathematics learning activities. Children’s mathematical abilities were assessed using a validated instrument covering numbers, classification, measurement, sequencing, geometry, and patterns. The data were analyzed using Two-Way Analysis of Variance (ANOVA) at a 0.05 level of significance. Findings: The results revealed significant main effects of both the RADEC learning model and local cultural integration on children’s mathematical development (p < .05). Learners exposed to RADEC-based instruction achieved higher mathematical performance compared to those receiving conventional instruction. Similarly, integrating cultural contexts significantly enhanced children’s conceptual understanding. However, no statistically significant interaction effect was found between the learning model and cultural integration. Significance: The findings provide empirical support for the role of structured constructivist pedagogy and culturally responsive instruction in early childhood mathematics education, offering practical implications for designing meaningful and context-based learning experiences.